Implementation of mobile game-transformed lecturebased approach to promoting C programming language learning - Kannika Daungcharone (2020)
Copyright © 2020 Inderscience Enterprises Ltd. Many studies have utilised the potential of mobile games to promote students’ learning performance, while few have transformed compiler working steps into mobile games. In this paper, the researchers developed a mobile game by simulating the C compiler working steps with daily life situations. Afterward, the researchers applied a lecture-based learning approach to implementing the game in a Thai university C programming language course. The group implemented a mobile game-transformed lecture-based approach by comparing it to conventional lecture-based approach and mobile game approach. The findings of this study support the notion that students can better achieve the C programming language concept through a mobile game, especially when integrated with the process of lecture-based approach. The findings of this study also highlight the mobile game-transformed lecture-based approach support the students’motivation to learn the C programming language.